2018
DOI: 10.1007/s00125-018-4675-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dapagliflozin and n-3 carboxylic acids on non-alcoholic fatty liver disease in people with type 2 diabetes: a double-blind randomised placebo-controlled study

Abstract: Aims/hypothesisThe EFFECT-II study aimed to investigate the effects of dapagliflozin and omega-3 (n-3) carboxylic acids (OM-3CA), individually or combined, on liver fat content in individuals with type 2 diabetes and non-alcoholic fatty liver disease (NAFLD).MethodsThis randomised placebo-controlled double-blind parallel-group study was performed at five clinical research centres at university hospitals in Sweden. 84 participants with type 2 diabetes and NAFLD were randomly assigned 1:1:1:1 to four treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
250
3
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 300 publications
(275 citation statements)
references
References 41 publications
13
250
3
9
Order By: Relevance
“…However, the number of participants with fibrosis or severe fibrosis was small, which affects the interpretability of these results. Extending recent data demonstrating the individual effects of GLP‐1RAs or SGLT2 inhibitors on NAFLD, the present results are the first to demonstrate the effect of this combination in reducing NAFLD biomarkers in people with type 2 diabetes, and indicate that combining these two agents may exert stronger beneficial effects on NAFLD than each drug alone. Moreover, as NAFLD is independently associated with cardiovascular disease, and the cardiovascular benefits of GLP‐1RAs and SGLT2 inhibitors are now well established, the EXE once weekly + DAPA combination may confer a reduction in cardiovascular risk in patients with type 2 diabetes and NAFLD.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…However, the number of participants with fibrosis or severe fibrosis was small, which affects the interpretability of these results. Extending recent data demonstrating the individual effects of GLP‐1RAs or SGLT2 inhibitors on NAFLD, the present results are the first to demonstrate the effect of this combination in reducing NAFLD biomarkers in people with type 2 diabetes, and indicate that combining these two agents may exert stronger beneficial effects on NAFLD than each drug alone. Moreover, as NAFLD is independently associated with cardiovascular disease, and the cardiovascular benefits of GLP‐1RAs and SGLT2 inhibitors are now well established, the EXE once weekly + DAPA combination may confer a reduction in cardiovascular risk in patients with type 2 diabetes and NAFLD.…”
Section: Discussionsupporting
confidence: 73%
“…However, in overweight, insulin‐resistant patients without type 2 diabetes, it has been reported that 12 weeks of DAPA treatment had no impact on hepatic steatosis despite a mean weight loss of 4.4 kg . Recent evidence suggests that DAPA reduces specific hepatocyte injury biomarkers, such as cytokeratin 18‐M30 and plasma fibroblast growth factor 21, suggesting an intrinsic disease‐modifying effect in NAFLD . Regarding hyperglycaemia, excess dietary sugars can induce liver glucotoxicity by increasing hepatic steatosis, via de novo lipogenesis, and exacerbating insulin resistance and cellular demise, through mechanisms including the activation of oxidative and endoplasmic reticulum stress responses .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, their impact on liver histology remains to be established. Table summarizes several recent RCTs in NAFLD . Taken together, this class has been remarkably consistent in causing a 2% to 3% decrease in total body weight (1.5‐3.0 kg) and in lowering plasma aminotransferases with a placebo‐corrected reduction in intrahepatic triglyceride content of 10%‐30%.…”
Section: The Future Of Treating Nash In Patients With T2dmmentioning
confidence: 83%